Impacts of anticipatory cash transfers in the context of weather disasters - Lukas Mogge; Julian Roeckert; Kati Krähnert (RWI - Leibniz-Institut für Wirtschaftsforschung, 2024)
Anticipatory humanitarian assistance is a novel approach to aid in the context of weather disasters, drawing on meteorological forecasts. Using a randomized study design, we analyze the impact of anticipatory cash transfers distributed to pastoralist households in Mongolia during an extreme winter event. We do not find overall effects on livestock assets, income, investments, or consumption across the study population. No heterogenous effects are found for different levels of disaster intensity. However, there is robust evidence that cash transfers benefited households with lower pre-treatment wealth. The paper concludes by highlighting practical challenges in evaluating (anticipatory) humanitarian interventions. – – Vorausschauende humanitäre Hilfe ist ein neuer Ansatz zur Unterstützung von Haushalten bei Extremwetterereignissen, der sich auf meteorologische Vorhersagen stützt. Mithilfe eines randomisierten Studiendesigns wird in dieser Studie die Wirksamkeit vorausschauender Geldtransfers, die während eines extremen Winterereignisses an Viehhalter in der Mongolei verteilt wurden, untersucht. Bei Betrachtung der gesamten Studienstichprobe können wir keine Effekte auf die Herdengröße, Einkommen, Investitionen oder Konsum feststellen. Weiterhin finden wir keine heterogene Effekte in Bezug auf die Intensität des Wetterereignisses. Es gibt jedoch robuste Belege dafür, dass Haushalte, die vor der Intervention über ein geringeres Vermögen verfügen, von den Geldtransfers profitieren. Abschließend werden in der Studie praktische Herausforderungen bei der Evaluierung von (vorausschauenden) humanitären Interventionen diskutiert.
Keywords: D61; O12; Q54; 330; Agriculture; anticipatory humanitarian assistance; extreme weather events; impact evaluation